RETRACTED: COP9 Signalosome CSN4 and CSN5 Subunits Are Involved in Jasmonate-Dependent Defense Against Root-Knot Nematode in Tomato - Shang, Yifen; Wang, Kaixin; Sun, Shuchang; Zhou, Jie; Yu, Jing-Quan (Frontiers in Plant Science, 2019)
COP9 signalosome is an evolutionarily conserved regulatory component of the ubiquitin-proteasome system that plays crucial roles in plant growth and stress tolerance; however, the mechanism of COP9-mediated resistance to root-knot nematode (RKN, Meloidogyne incognita) is not fully understood in plants. In the present study, we found that RKN infection in the roots rapidly increased the transcript levels of COP9 signalosome subunit 4 and 5 (CSN4 and CSN5) and their protein accumulation in tomato (Solanum lycopersicum) plants. Suppression of CSN4 or CSN5 expression which resulted in significantly increased the numbers of egg masses and aggravated RKN-induced lipid peroxidation of cellular membrane, but inhibited RKN-induced accumulation of CSN4 or CSN5 protein in tomato roots. Importantly, the RKN-induced accumulation of jasmonic acid (JA) and JA-isoleucine (JA-Ile), and the transcript levels of JA-related biosynthetic and signaling genes were compromised by CSN4 or CSN5 gene silencing. Moreover, protein-protein interaction assays demonstrated that CSN4 and CSN5B interact with Jasmonate ZIM domain 2 (JAZ2) which is the signaling component of JA pathway. Silencing of CSN4 or CSN5 also compromised RKN-induced JAZ2 expression in CSN4 or CSN5 gene-silenced plants. Together, our findings indicate that CSN4 and CSN5 play critical roles in JA-dependent basal defense against RKN.